(untitled) (International Journal of Language, Literacy and Translation, 2025)
The exploration of gender issues in the field of translation encompasses a complex array of linguistic, cultural, and socio-political dimensions. Since the 1990s, there has been a growing emphasis on gender-related concerns within translation studies. However, a comprehensive review of the literature on current trends and research challenges in this area remains lacking. To bridge this gap, the current study employs the PRISMA framework to conduct a systematic literature review, drawing on databases such as Google Scholar and Scopus for data retrieval. This review focuses on a variety of topics, including seminal works, the most cited articles, the primary interests of feminist theorists, key research objectives, and findings. Utilizing a qualitative review methodology, this study aims to provide insights into the predominant themes explored to date and identify future research directions, particularly concerning feminist theories and language. A content analysis of 15 selected papers from peer-reviewed international journals published between 2002 and 2022 was conducted. These papers were chosen based on their relevance to the research question, the representativeness of the topic, and their scholarly quality. The findings highlight a significant increase in the depiction of gender in literary translation over the past five years, especially regarding the translation of gender stereotypes. This research presents a systematic overview of the field, offering conclusions on trends, results, methodological approaches, and challenges faced. Key findings include an increased focus on the study of internal language processing, the observation of inconsistent effects, and the identification of a notable disparity in the reliability of translations between individuals who identify as male and female.